PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Bagian Operasi Terminal PT. (persero) PELINDO III Terminal Petikemas Semarang) - Muhammad Nur Isna; Rodhiyah Rodhiyah; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
Every organization which is either serving the public interest as State-owned Corporation, government or private organization, want to get maximum achievement from their employee’s performance, result improvement and attain the goal of organization. From the performance’s appraisal there is still unfulfilled working standard so that is why the organization made company working plan. Referring to the decreasing of export import flow and unfulfilled working standard reflect to the influence of compensation and work environment toward employee’s performance.The aim of the study is to determine the effect of compensation and working environment toward employee's performance at Container Terminal of PT (Persero) PELABUHAN INDONESIA III Semarang.The type of the study is explanatory, which is the technique of collecting data throughquestionnaires. Sampling using Slovin formula by using purposive sampling techniques which taken from 93 people from Terminal Operation Division employees. Method of analysis used in this study is Quantitative Data Analysis.From the result of the study showed that compensation has significantly positive and powerful effect toward employee’s performance which also 36% for contribution given and the working environment has beneficial and strong effect toward employee’s performance which also 47.5% for contribution given.  From the result of the study the writer concludes that compensation and working environment have positive effect toward employee’s performance besides it has strong influence toward employee’s performance which is showed 0.724.